Heat balance modelling and simulation of non-mixing buffer tank design for hydronic heating applications. (1st April 2022) - Li, Simon; Berrio, Denering; Fang, Yanda
Abstract: The purpose of this paper is twofold. First, it aims to develop a theoretical model for a non-mixing buffer tank system for hydronic heating applications. The traditional buffer tanks often involve water mixing where the boiler's hot water is mixed with the system's return water. This practice reduces the temperature differences (ΔT) through the boilers and the in-space heating equipment, bringing in concerns of their thermal performance. To address this concern, the non-mixing buffer tank system is designed with a movable separation plate in a buffer tank, which can store supply hot water and return cold water separately. The theoretical model of the non-mixing design explores the dynamics of water temperatures and the interactions of system components. As the second purpose, this paper then conducts a simulation study to compare both mixing and non-mixing designs under the same heating loads. As a result, it is observed that the non-mixing design can achieve better system efficiency (e.g., 86.7% versus 82.0% for low heating loads) due to better average boiler's efficiency (90.5% versus 86.8%) and longer cycle period (37.85 min vs. 9.27 min). In addition, the non-mixing design allows better control of supply water temperature, which can better support the outdoor reset control of boilers. Highlights: Non-mixing buffer tank improves the thermal potential of hydronic heating systems. The properties of the non-mixing design are described through heat balance modelling. The non-mixing design yields better system efficiency and supports better system control.